The Role of Regular Physical Therapy on Spasticity in Children With Cerebral Palsy - Heewon Lee; Eun Kyung Kim; Dong Baek Son; Youngdeok Hwang; Joon-Sung Kim; Seong Hoon Lim; Bomi Sul; Bo Young Hong (Annals of Rehabilitation Medicine, 2019)
Objective To investigate the effect of physical therapy (PT) intervention on spasticity in patients with cerebral palsy (CP), and to assess the degree of deterioration of spasticity when regular PT is interrupted in those patients. Methods We recruited 35 children with spastic CP who visited our hospital for PT, and whose Modified Tardieu Scale (MTS) scores were serially recorded including before and after a 10-day public holiday time frame period. The outcome measures were the angle of range of motion (ROM) of dorsiflexion of the ankle joint (R1 and R2) in the knee flexion and extension positions as assessed using the MTS. Results The range of dorsiflexion of the ankle joint (R1 and R2) after the holiday period was significantly decreased as compared with that measured ROM noted before the holiday period, regardless of the knee position, age, or gross motor function. The dynamic component of the MTS (R2–R1) showed a slight decrease in the knee flexion position. Conclusion Interruption of regular PT aggravated spasticity and decreased ankle joint ROM in children with spastic CP. Our findings suggest that regular PT in the care continuum for children with CP is crucial for the maintenance of ROM in the spastic ankle joints.